2003
DOI: 10.1053/ejvs.2002.1885
|View full text |Cite
|
Sign up to set email alerts
|

Venous disease is associated with an impaired range of ankle movement*

Abstract: limbs with venous hypertension have a reduced range of ankle movement related to the clinical severity of venous disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
81
0
4

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(88 citation statements)
references
References 18 publications
3
81
0
4
Order By: Relevance
“…Some did not attend for their operation and others underwent surgery under local anaesthetic without stripping of the long saphenous vein. Factors other than venous reflux, such as coexisting medical problems or ankle stiffness causing poor calf muscle function, 34 may have contributed to recurrent ulceration in individual cases. Whether these patients experienced more ulcer free time after surgery as a result of less frequent or shorter episodes of recurrent ulceration remains unproved.…”
Section: Discussionmentioning
confidence: 99%
“…Some did not attend for their operation and others underwent surgery under local anaesthetic without stripping of the long saphenous vein. Factors other than venous reflux, such as coexisting medical problems or ankle stiffness causing poor calf muscle function, 34 may have contributed to recurrent ulceration in individual cases. Whether these patients experienced more ulcer free time after surgery as a result of less frequent or shorter episodes of recurrent ulceration remains unproved.…”
Section: Discussionmentioning
confidence: 99%
“…According to self-reports, functional status is diminished in these patients [36,39] also because of some physical dysfunctions, like abnormalities in gait [45], impaired balance, peripheral neuropathy [43,46] weak leg muscles (plantar flexion and dorsiflexion muscles) [29,30,45], or diminished ankle range of motion [10,30,47]. These dysfunctions are also associated with impaired muscle pump function in the lower extremity [43], an important risk factor for venous ulceration [48].…”
Section: Functional and Hrql Implications Of Cvdmentioning
confidence: 99%
“…Patients with CVD present limited ankle range of motion [36,45,47,78,98]. Diminished ankle mobility tends to aggravate as CVD progresses and in parallel with increasing severity of symptoms, thus further contributing to a poor CMPF [78,98].…”
Section: Impairment Of Calf Muscle Pump and Functional Capacitymentioning
confidence: 99%
See 1 more Smart Citation
“…135 Thus, heel-toe walking produces optimal calf muscle pump function. 135 Moreover, ankle range of motion has been significantly correlated with severity of venous insufficiency 136,137 and this may be related to the observed impaired calf muscle function in patients with venous disease. 138 Importantly, a single-arm pilot study and two small randomized control trials indicated that exercises that increase calf muscle strength and mobility also improve calf muscle function.…”
Section: Translations/interventionsmentioning
confidence: 99%